ANALISIS KARAKTERISTIK LINGKUNGAN PEMUKIMAN KUMUH DI KELURAHAN BELAWAN BAHAGIA, KECAMATAN MEDAN BELAWAN - Dewi Nelly Simanjuntak (Jurnal Samudra Geografi, 2022)
It is very important to know the characteristics of the residential environment, because the growth of the residential environment has increased very rapidly due to high population growth. The higher population growth results in the need for greater settlements, causing the growth of slums. Slums are settlements that are not suitable for habitation, and do not meet the standards of healthy settlements. The social condition of the population is generally low, the facilities and infrastructure are not yet adequate. If these conditions are not controlled growth, then the quality of the environment and public health will continue to decline. This study aims to determine the environmental characteristics of slums in Belawan Bahagia Village, Medan Belawan District. The method used is data collection through observation, a list of questionnaires, interviews and data collection from relevant agencies to complete the results of existing surveys. The results of the survey are the density of population settlements with very close distances between buildings, the condition of the building does not meet health requirements, Building irregularities are residential buildings that do not meet the building layout provisions in the Detailed Spatial Planning and Environmental Building Plans. the average community needs clean water using drilled wells and buying from neighbors. Drainage that doesn't work well and is very dirty. wastewater treatment is very poor and has a habit of throwing garbage directly into the river. The average livelihood of the community is working as fishermen and traders with an average income of IDR 500,000 to IDR 1,000,000. The pattern of population settlements is an elongated (linear) shape following roads and rivers.